A Universal Base in a Specific Role: Tuning up a Thrombin Aptamer with 5-Nitroindole - Tsvetkov, Vladimir B. (Sci Rep, 2015)
In this study we describe new modified analogs of the thrombin binding aptamer (TBA) containing 5-nitroindole residues. It has been shown that all modified TBAs form an anti-parallel G-quadruplex structure and retain the ability to inhibit thrombin. The most advanced TBA variant (TBA-N8) has a substantially increased clotting time and two-fold lower IC(50) value compared to the unmodified prototype. Molecular modelling studies suggest that the improved anticoagulant properties of TBA-N8 result from changes in the binding mode of the analog. A modified central loop in TBA-N8 is presumed to participate in the binding of the target protein. Studies of FAM labelled TBA and TBA-N8 showed an improved binding affinity of the modified aptamer and provided evidence of a direct interaction between the modified central loop and thrombin. Our findings have implications for the design of new aptamers with improved binding affinities.